2019
DOI: 10.1121/1.5087555
|View full text |Cite
|
Sign up to set email alerts
|

Determining the energetic and informational components of speech-on-speech masking in listeners with sensorineural hearing loss

Abstract: The ability to identify the words spoken by one talker masked by two or four competing talkers was tested in young-adult listeners with sensorineural hearing loss (SNHL). In a reference/baseline condition, masking speech was colocated with target speech, target and masker talkers were female, and the masker was intelligible. Three comparison conditions included replacing female masker talkers with males, time-reversal of masker speech, and spatial separation of sources. All three variables produced significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 63 publications
3
26
0
Order By: Relevance
“…(2001) where the number of concurrent talkers was increased to four. Consistently, several later studies also reported a large masking release due to dissimilar target/masker sex ( Noble and Perrett, 2002 ; Brungart and Simpson, 2002 ; Allen et al., 2008 ; Brungart et al., 2001 , 2009 ; Cullington and Zeng 2008 ; Zekvel et al., 2014 ; Xia et al., 2015 ; Kidd et al., 2016 , 2019 ; Rennies et al., 2019 ; Zhang et al., 2020 ).…”
Section: Speech Unmasking In Englishsupporting
confidence: 68%
“…(2001) where the number of concurrent talkers was increased to four. Consistently, several later studies also reported a large masking release due to dissimilar target/masker sex ( Noble and Perrett, 2002 ; Brungart and Simpson, 2002 ; Allen et al., 2008 ; Brungart et al., 2001 , 2009 ; Cullington and Zeng 2008 ; Zekvel et al., 2014 ; Xia et al., 2015 ; Kidd et al., 2016 , 2019 ; Rennies et al., 2019 ; Zhang et al., 2020 ).…”
Section: Speech Unmasking In Englishsupporting
confidence: 68%
“…In addition, they benefit less from amplitude modulations in noise signals (Bacon et al., 1998; George et al., 2006) or from spatial separation of multiple competing signals ( Hornsby et al., 2006 ). These differences are likely due to a reduced ability to process temporal and spatial cues ( Arbogast et al., 2005 ; Johannesen et al., 2016 ; Kidd et al., 2019 ; Lőcsei et al., 2016 ). As pointed out earlier, current HA fittings focus on the pure-tone audiogram and therefore neglect suprathreshold hearing deficits.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of listeners to reliably perceive talker gender can have important implications for speech intelligibility, particularly under speech-on-speech masking conditions. Previous studies have provided clear evidence that gender differences between target and masker talkers typically result in a substantial release from masking, allowing listeners to successfully understand target speech at significantly lower target-to-masker ratios (e.g., Brungart, 2001 ; Kidd et al , 2016 ; Kidd et al , 2019 ). Any alteration/distortion of the speech signal that renders it more difficult for a listener to distinguish talker gender deprives the listener of that powerful source segregation cue and could diminish the typical release from masking that would otherwise occur.…”
Section: Introductionmentioning
confidence: 99%